2010
DOI: 10.1002/prca.200900063
|View full text |Cite
|
Sign up to set email alerts
|

Decreased annexin A3 expression correlates with tumor progression in papillary thyroid cancer

Abstract: Decreased expression of ANXA3 in papillary thyroid cancer supports the idea that ANXA3 may be an effective marker of microcarcinoma, and a negative predictor of papillary thyroid cancer progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 24 publications
0
24
1
Order By: Relevance
“…It has been reported that Annexins, such as Annexin A1, A2 A3, A5 and A7, are closely associated with cancers [20]. In this study, we detected these five Annexins genes in CRC tissues.…”
Section: Resultsmentioning
confidence: 64%
“…It has been reported that Annexins, such as Annexin A1, A2 A3, A5 and A7, are closely associated with cancers [20]. In this study, we detected these five Annexins genes in CRC tissues.…”
Section: Resultsmentioning
confidence: 64%
“…Although it has not been extensively studied in NPC cells, annexin A3 has prognostic relevance in prostate cancer (20), lung adenocarcinoma (21) and papillary thyroid cancer (22). Skvortsova et al (6) identified annexin A2 and A3 as novel biomarkers in prostate cancer cell lines using two-dimensional difference gel electrophoresis and matrix-assisted laser desorption ionization time-of-flight (TOF)/TOF-mass spectrometry; however, annexin A3 was not verified.…”
Section: Discussionmentioning
confidence: 99%
“…It has three different domain composition: a short The C-terminus domain including four conserved ‘annexin repeat’ domains I, II, III and IV, a repeated collagen-like sequence, and a COOH-terminal domain including a single carbohydrate recognition-binding domain [1415]. It is a membrane associated protein involved in the regulation of varieties of biological responses, containing cell proliferation, angiogenesis, cancer progression and metastasis [1618]. ANXA3has been identified as a putative tumor oncogene in a diversity of carcinomas, such as Ovarian carcinoma, Lung adenocarcinoma, hepatocellular carcinoma, Colorectal cancer [1922].…”
Section: Introductionmentioning
confidence: 99%